Achieving the Millennium Development Goals: A measure of progress - Degol Hailu; Raquel Tsukada (International Policy Centre for Inclusive Growth (IPC-IG), 2011)
This paper introduces a methodology that measures the effort made by countries in achieving the Millennium Development Goals (MDGs). The methodology compares the rate of progress on MDG indicators in the period before and after the adoption of the MDGs. We correct for two biases ignored in previous methodologies: non-linearity in the rate of change, and effort appreciation. By correcting for the first, we recognise that the rate of progress in MDG indicators is not linear across time. As for the second bias, we note that natural constraints hinder countries from achieving the targets as they approach their upper or lower bound limits. These two corrections allow us to identify countries that are making respectable progress on MDG acceleration, despite their likely failure in achieving the Goals by 2015.
Keywords: 330; Millennium Development Goals